Intrinsic motivations of public sector employees: Evidence for Germany - Robert Dur; Robin Zoutenbier (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
We examine differences in altruism and laziness between public sector employees and private sector employees. Our theoretical model predicts that the likelihood of public sector employment increases with a worker·s altruism, and increases or decreases with a workers laziness depending on his altruism. Using data from the German Socio-Economic Panel Study, we find that public sector employees are significantly more altruistic and lazy than observationally equivalent private sector employees. A series of robustness checks show that these patterns are stronger among higher educated workers; that the sorting of altruistic people to the public sector takes place only within the caring industries; and that the difference in altruism is already present at the start of peoples career, while the difference in laziness is only present for employees with sufficiently long work experience.
Keywords: H1; J45; M5; 330; public service motivation; altruism; laziness; sorting; public sector employment; personality characteristics